Piezo1 Channels as Force Sensors in Mechanical Force-Related Chronic Inflammation - Liu, Hailin; Hu, Jialing; Zheng, Qingcui; Feng, Xiaojin; Zhan, Fenfang; Wang, Xifeng; Xu, Guohai; Hua, Fuzhou (Frontiers in Immunology, 2022)
Abstract Mechanical damage is one of the predisposing factors of inflammation, and it runs through the entire inflammatory pathological process. Repeated or persistent damaging mechanical irritation leads to chronic inflammatory diseases. The mechanism of how mechanical forces induce inflammation is not fully understood. Piezo1 is a newly discovered mechanically sensitive ion channel. The Piezo1 channel opens in response to mechanical stimuli, transducing mechanical signals into an inflammatory cascade in the cell leading to tissue inflammation. A large amount of evidence shows that Piezo1 plays a vital role in the occurrence and progression of chronic inflammatory diseases. This mini-review briefly presents new evidence that Piezo1 responds to different mechanical stresses to trigger inflammation in various tissues. The discovery of Piezo1 provides new insights for the treatment of chronic inflammatory diseases related to mechanical stress. Inhibiting the transduction of damaging mechanical signals into inflammatory signals can inhibit inflammation and improve the outcome of inflammation at an early stage. The pharmacology of Piezo1 has shown bright prospects. The development of tissue-specific Piezo1 drugs for clinical use may be a new target for treating chronic inflammation.